Quantitative studies of vaginal bacteria. - Masfari, A N (1986)
A quantitative method of culture, based on a weighed sample and with results expressed as colony forming units (cfu)/g was assessed and used to investigate the vaginal flora of normal women and that of women with vaginal disease. Samples were collected by means of disposable plastic loops into modified proteose peptone water transport medium in preweighed bottles. Counts expressed as cfu/g of secretion were consistent, whereas counts expressed as cfu/ml were inconsistent. Results obtained with specimens manipulated on the open bench were the same as those from duplicate samples processed in an anaerobic chamber. The normal vaginal flora was predominantly aerobic--lactobacilli, coryneforms, and coagulase negative staphylococci--with counts of greater than or equal to 10(8) cfu/g for lactobacilli. These were also present in patients with candidosis, but the flora in patients with trichomoniasis, bacterial vaginosis, gonorrhoea, or chlamydial infection was predominantly anaerobic. The commonest anaerobes were Bacteroides spp, particularly B bivius; they were found in 55% of controls but at counts of 10(2) cfu/g lower than in the patients, most of whom had high counts of anaerobes (greater than 10(8) cfu/g). The isolation rate of Gardnerella vaginalis was not appreciably greater from patients with bacterial vaginosis, and the quantitative cultures on controls and patients who were G vaginalis positive were the same (approximately equal to 10(7) cfu/g). Quantitative studies show greater differences than qualitative cultures between normal controls and patients with vaginal infections, indicating that some symptoms and signs of such infections may be related to quantitative polymicrobial changes.